Additions to the knowledge of the diversity of conidial fungi in the montane cloud forest of the state of Veracruz. II - Heredia Abarca, Gabriela; Arias Mota, Rosa Ma.; Mena-Portales, Julio; Mercado-Sierra, Ángel (Instituto de Ecología, A.C., 2006)
This paper is part of an ongoing series of taxonomic investigations documenting the richness of conidial fungi occurring on plant debris in the cloud forests of Veracruz, Mexico. In the present paper 18 species are described; 15 of which are new to Mexico, and three were collected for the first time in a cloud forest habitat.